2010
DOI: 10.1021/jz100817z
|View full text |Cite
|
Sign up to set email alerts
|

DNA Encapsulation of 10 Silver Atoms Producing a Bright, Modulatable, Near-Infrared-Emitting Cluster

Abstract: Photostability, inherent fluorescence brightness, and optical modulation of fluorescence are key attributes distinguishing silver nanoclusters as fluorophores. DNA plays a central role both by protecting the clusters in aqueous environments and by directing their formation. Herein, we characterize a new near infrared-emitting cluster with excitation and emission maxima at 750 and 810 nm, respectively that is stabilized within C 3 AC 3 AC 3 TC 3 A. Following chromatographic resolution of the near infrared speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
213
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(223 citation statements)
references
References 36 publications
10
213
0
Order By: Relevance
“…Silver and phosphorus standards (High Purity Standards) were used to generate calibration curves, and control samples containing oligonucleotide and Ag + were used to account for matrix effects. 50 A peristaltic pump delivered the samples to the nebulizer and the argon plasma. To relate the phosphorus and oligonucleotide concentrations, the lengths were derived from the DNA sequences, after accounting for the absence of the 3′ terminal phosphate.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Silver and phosphorus standards (High Purity Standards) were used to generate calibration curves, and control samples containing oligonucleotide and Ag + were used to account for matrix effects. 50 A peristaltic pump delivered the samples to the nebulizer and the argon plasma. To relate the phosphorus and oligonucleotide concentrations, the lengths were derived from the DNA sequences, after accounting for the absence of the 3′ terminal phosphate.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…It has been shown that the emission wavelength can be varied from violet to near infrared in DNA-AgNCs. [19][20][21][22] Therefore, DNA-AgNCs have been identified as potential candidates to be utilized in various applications such as bioimaging, biolabeling, catalytic reactions, and analyte and ligand sensing. [4][5][6][7]14,[23][24][25][26] The emission tunability can also be altered through experimental conditions, 19,20,27,28 but changing the DNA template itself is considered superior due to the higher functionality in the DNA-AgNCs through emission tuning.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, we focus on the nearinfrared emitters using 633 nm as the excitation wavelength. Although a number of single molecule studies have been performed on AgNC to investigate specifi c photophysical parameters, [ 5,6,8,10,14,25,[27][28][29][30][31][32][33] we simultaneously measure several photophysical properties for each individual cluster, including decay times, emission spectra, and antibunching. This allows us to compare and correlate these photophysical properties within a sample to better understand the photophysical behavior and heterogeneity of these complex as-synthesized AgNC samples.…”
Section: Introductionmentioning
confidence: 99%